Formation of polycyclic aromatic hydrocarbons and heterocyclic amines in gas-grilled honey-spices marinated beef satay - Ahmad Kamal, Nor Hasyimah (2020)
Polycyclic aromatic hydrocarbons (PAHs) and heterocyclic amines (HCAs) are cooking toxicants that have been associated with elevated malignancy risk due to consumption of grilled red meat. They are simultaneously generated in satay due to high temperature grilling process. The objectives of this study were: a) To determine the effects of temperature on simultaneous formation of PAHs and HCAs in gas-grilled beef satay, b) To evaluate the effects of honey-spices marination on simultaneous formation of PAHs and HCAs. Unmarinated samples were used as control. Fifteen PAHs were determined using high performance liquid chromatography with fluorescence detection method (HPLC-FLD) and nine HCAs were quantified using liquid chromatography tandem-mass spectrometry (LC-MS/MS) with gradient programme. Solid-phase extraction (SPE) method was used for sample clean-up. The natural precursors in raw beef satay samples were analysed to reflect on the formations of PAHs (fats) and HCAs (free amino acids, sugars, and creatinine). For the first objective, beef satay were grilled at 150°C, 200°C, 250°C, 300°C, 350°C. The lowest concentrations of PAHs and HCAs were significantly (P<0.05) generated at 150°C as the formation of PAHs and HCAs increased simultaneously with temperatures. Benzo[a]pyrene were detected in all samples and increased markedly at 300°C and 350°C. The sums of 4 PAHs (PAH4) in marinated beef satay at 300°C and 350°C exceeded maximum level in Commission Regulation (EU) 2015/1125. Significant reductions of polar and non-polar HCAs, except 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) were detected in marinated beef satay across all temperatures. The second objective of this study used two different honey-spices (Apis mellifera honey-spices and Trigona sp.honey-spices) marinades at grilling temperature of 150°C, 250°C, and 350°C. The formation of PAHs (marinated beef satay) and HCAs (control) were the highest (P<0.05) at 350°C. The most prominent PAHs were phenanthrene (24.61–84.36 ng/g) and fluoranthene (10.00–36.52 ng/g) while HCA was 9H-pyrido[4,3-b]indole (2.67–393.89 ng/g). Both honey-spices marinations significantly (P<0.05) reduced naphthalene, fluorene, and pyrene (PAHs), and 2-amino-9H-pyrido[2,3-b]indole, 1-methyl-9H-pyrido[4,3-b]indole, and 9H-pyrido-[4,3-b]indole (HCAs) in gas-grilled beef satay across all temperatures. However, 2-amino-3,7,8-trimethylimidazo[4,5-f]quinoxaline (7,8-DiMeIQx) were not detected in any marinated samples. Partial least squares regression (PLSR) revealed significant positive correlations among precursors (raw beef satay samples) with PAHs and HCAs, respectively. Overall, it is concluded that overall formation of fifteen PAHs and nine HCAs simultaneously in gas-grilled beef satay samples increased with grilling temperatures. Formation of PAHs revealed inverse quantitative profiles in contrast with HCAs in marinated beef satay. Honey-spices marination prior to grilling reduced the formation of HCAs; on the contrary, do not present the same effect in the production of PAHs in grilled beef satay.